2006
DOI: 10.5194/angeo-24-915-2006
|View full text |Cite
|
Sign up to set email alerts
|

A modeling study of ionospheric F2-region storm effects at low geomagnetic latitudes during 17-22 March 1990

Abstract: Abstract.We have presented a comparison between the modeled NmF2 and hmF2, and NmF2 and hmF2, which were observed in the low-latitude ionosphere simultaneously by the Kokubunji, Yamagawa, Okinawa, Manila, Vanimo, and Darwin ionospheric sounders, by the middle and upper atmosphere (MU) radar during 17-22 March 1990, and by the Arecibo radar for the time period of 20-22 March 1990. A comparison between the electron and ion temperatures measured by the MU and Arecibo radars and those produced by the model of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 88 publications
(111 reference statements)
2
11
0
Order By: Relevance
“…The negative storm response during the pre-storm phenomenon in equatorial region and mid latitude may be as a result of large northward value of electric field and large southward turning of interplanetary magnetic field (IMF) Bz. Many research has been carried out on the positive and negative ionospheric disturbances at the mid-and highlatitude using different modelling and method (Rakhee et al 2010;Mukherjee et al 2010;Romanova et al 2008;Rishbeth and Mendillo 2001;Bencze et al 2004;Tsagouri et al 2000;Namgaladze et al 2000;Vasiljevic and Cander 1996), with only few mention on equatorial region (Mansilla 2011;Prölss 2006;Pavlov et al 2006), the result confirmed prompt effects of geomagnetic disturbances at all latitudes. The recent research on ionospheric F2 region have confirmed a pronounce effect of geomagnetic storm on low latitude ionosphere.…”
Section: Discussionsupporting
confidence: 84%
“…The negative storm response during the pre-storm phenomenon in equatorial region and mid latitude may be as a result of large northward value of electric field and large southward turning of interplanetary magnetic field (IMF) Bz. Many research has been carried out on the positive and negative ionospheric disturbances at the mid-and highlatitude using different modelling and method (Rakhee et al 2010;Mukherjee et al 2010;Romanova et al 2008;Rishbeth and Mendillo 2001;Bencze et al 2004;Tsagouri et al 2000;Namgaladze et al 2000;Vasiljevic and Cander 1996), with only few mention on equatorial region (Mansilla 2011;Prölss 2006;Pavlov et al 2006), the result confirmed prompt effects of geomagnetic disturbances at all latitudes. The recent research on ionospheric F2 region have confirmed a pronounce effect of geomagnetic storm on low latitude ionosphere.…”
Section: Discussionsupporting
confidence: 84%
“…The ionosphere at the geomagnetic equator and low geomagnetic latitudes have been studied observationally and theoretically for many years (see Moffett, 1979;Anderson, 1981;Walker, 1981;Anderson et al, 1996;Bailey and Balan, 1996;Millward et al, 1996;Roble, 1996;Richards and Torr, 1996;Schunk and Sojka, 1996;Rishbeth, 2000;Abdu, 1997Abdu, , 2001Huba et al, 2000;Fesen et al, 2002;Maruyama et al, 2003;Pavlov et al, 2006, and references therein). The behaviour of the equatorial and low-latitude ionosphere is strongly dependent upon the meridional component (which is located in a plane of a geomagnetic meridian) of a drift velocity, V E =E×B/B 2 , of electrons and ions perpendicular to the geomagnetic field, B, due to an electric field, E, which is generated in the E region.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown by Su et al (1997) that the difference in time of occurrence between the peak value of the pre-reversal increase in the E Â B drift and in the peak values of TEC and NmF2 at equinox under solar-maximum conditions at the crests of the equatorial anomaly varies with longitude because of the longitudinal difference of the neutral wind. It is shown for the first time by Pavlov et al (2006) that the nighttime weakening of the equatorial zonal electric field (in comparison with that produced by the empirical model of Fejer and Scherliess (1997) or Scherliess and Fejer (1999)) in combination with the corrected wind-induced plasma drift along magnetic field lines provides the development of the nighttime enhancements in NmF2 observed over Manila during the geomagnetically quiet-time conditions of 17 March 1990 and the geomagnetically storm-time period of 18-22 March 1990. The first purpose of this study is to find the physical mechanism and to study the relative role of the physical processes responsible for anomalous nighttime electron density enhancements observed by the Manila ionospheric sounder during 22-26 April 1990 using a time-dependent two-dimensional model of the low-and middlelatitude ionosphere and plasmasphere described in Section 2.…”
Section: Introductionmentioning
confidence: 94%
“…Pavlov et al (2004b found that weak differences between disturbed and quiet E Â B plasma drifts cannot be responsible for the suppression of the equatorial anomaly on 26 August 1987, and this suppression stems from the action of stormtime changes in neutral winds and densities on the equatorial anomaly development. On the other hand, Pavlov et al (2006) found that, during the most part of the geomagnetic storm-time period of 18-22 March 1990, the predominant sources of the suppression of the equatorial anomaly are related to both the neutral wind circulation and the differences between the used corrected equatorial zonal electric field and that produced by the empirical model of Scherliess and Fejer (1999). The second purpose of this work is to study the relative role of the disturbed thermospheric wind, electric field, neutral composition, and neutral temperature in the development and inhibition of the equatorial anomaly during the geomagnetic storm-time period of 22-26 April 1990 at solar maximum in the present case study, in which the electron density and temperature are measured simultaneously by the MU radars, and NmF2 and hmF2 are observed by the Kokubunji, Okinawa, Manila, Vanimo, and Darwin ionospheric sounders.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation